Frontiers in antennas next generation design & engineering - Gross, Frank B. (McGraw-Hill, 2011)
Edited by one of the world's foremost authorities on smart antennas and featuring contributions from global experts, Frontiers in Antennas discusses the latest advances in antenna design and engineering. This pioneering guide deals primarily with frontier antenna designs and frontier numerical methods. Many of the concepts presented have emerged within the last few years and are still in a rapid state of development. Each chapter provides in-depth details on a different unique and modern antenna technology